Narrative inquirers in the midst of meaning-making interpretive acts of teacher educators - Chan, Elaine; Keyes, Dixie; Ross, Vicki (Advances in research on teaching ;, 2012)
Narrative Inquirers in the Midst of Meaning-making: Interpretive Acts of Teacher Educators illustrates interim narrative field texts of identity as 'teacher educator stories' and demonstrates how researchers utilize common places of temporality, sociality, and place in analyzing narratives. It describes conceptualizations of narrative research processes, bringing forward narrative tools and methods of layering narratives from experienced narrative researchers. Through the metaphor of braided rivers, the chapters are woven together through unique chapter interim dialogues which spotlight the insights discovered within the three-dimensional inquiry space. From chapters on the temporal dimension of narrative inquiry, on burrowing and broadening through narrative, on openness and inconclusivity in interpretation, on plotlines discovered through the interpretive tool of chronotypes, and on the cross-cultural interpretation of field texts, researchers and teacher educators can reach new conclusions about the ontology and epistemology of narrative research, in the midst of meaning-making.